Between Exu and the Devil: The Discourse of “Occultist Umbanda” in Literature and the Continuity of Demonization: Between Exu and the Devil: The Discourse of “Occultist Umbanda” in Literature and the Continuity of Demonization (Élisée - Revista de Geografia da UEG, 2025)
This study analyzes the construction of a discursive field that we term “Occultist Umbanda,” formed between the 1950s and 1980s by Umbanda intellectuals such as Aluízio Fontenelle, Teixeira Neto, and José Bittencourt. Influenced by European esoteric currents and the occultist literature of Eliphas Levi, these authors developed narratives that associated Exu with the Christian Devil, reinforcing a long-standing tradition of demonizing this entity that can be traced from colonial accounts to the earliest scholarly studies of Afro-Brazilian religions. Through an analysis of their works, we observe the systematization of demonological hierarchies and an effort to legitimize the presence of Exu and Pomba-gira in the rituals of Umbanda and Quimbanda. The study demonstrates how this discourse both sustained a negative imaginary surrounding Exu and introduced relativizations of the concepts of good and evil, interpreting the practice of evil as a means toward the realization of good. Ultimately, the article concludes that “Occultist Umbanda” does not correspond to a consolidated ritual practice in religious communities, but rather to an intellectual elaboration that illustrates the tensions between popular religiosity, European occultism, and the social conflicts surrounding Afro-Brazilian religions in Brazil.
Keywords: Umbanda. Quimbanda. Exu. Occultism.